Water Allocation Strategies for the Kat Basin in South Africa : Comparing Negotiation Tools and Game Theory Models - Dinar, Ariel; Farolfi, Stefano; Patrone, Fioravante; Rowntree, Kate (World Bank, Washington, DC, 2012)
Governments and developing agencies promote participatory approaches in solving common pool resource problems, such as in the water sector. Two main participatory approaches have been applied separately, namely negotiation and mediation. In this paper the authors apply the Role-Playing Game that is a component of the Companion Modeling approach, a negotiation procedure, and the Cooperative Game Theory (Shapley value and the Nucleolus solution concepts) that can be mirrored as a mediated mechanism to a water allocation problem in the Kat watershed in South Africa. While the absolute results of the two approaches differ, the negotiation and the cooperative game theory provide similar shares of the benefit allocated to the players from various cooperative arrangements. By evaluating the two approaches, the authors provide useful tips for future extension for both the Role-Playing Games and the Cooperative Game Theory applications.